Study of construction and maintenance of slope in Klang Valley highway / Nadzren Ahayalimudin - Ahayalimudin, Nadzren (Faculty of Architecture, Planning and Surveying, 2009)
Slope stabilization may come in various types and material, but the purpose of construction of slope stabilization is to directly control slope from landslide to occur and strengthen soil mechanically. Therefore, the slope stabilization design must be able to withstand the bearing force of the slope and harsh of the weather. The dissertations shall focus on factor influence selection of right method of slope stabilization, method slope stabilization that have use in Klang Valley highway and maintenance method of slope in Klang Valley in this highway: 1. Rawang- Kuala Lumpur Highway. 2. Shah Alam Expressway. 3. New Klang Valley Expressway. Based on the interview and observation, it can be said that there is several types of slope stabilization, factor of selection are based on environment factor of the slope such as types of soil, degree of slope etc. Information about the maintenance of the slope also been identify to make sure that slope it in good condition and cannot risking the user of the highway.